Functional characterization of the Ucp1-associated oxidative phenotype of human epicardial adipose tissue. Issue 1 (December 2017) - Chechi, Kanta; Voisine, Pierre; Mathieu, Patrick; Laplante, Mathieu; Bonnet, Sébastian; Picard, Frédéric; Joubert, Philippe; Richard, Denis
Abstract Brown fat presence and metabolic activity has been associated with lower body mass index, higher insulin sensitivity and better cardiometabolic profile in humans. We, and others, have previously reported the presence ofUcp1, a marker of brown adipocytes, in human epicardial adipose tissue (eAT). Characterization of the metabolic activity and associated physiological relevance ofUcp1 within eAT, however, is still awaited. Here, we validate the presence ofUcp1 within human eAT and its 'beige' nature. Usingin-vitro analytical approaches, we further characterize its thermogenic potential and demonstrate that human eAT is capable of undergoing enhanced uncoupling respiration upon stimulation. Direct biopsy gene expression analysis reveals a negative association between thermogenic markers and oxidative stress-related genes in this depot. Consistently, isoproterenol (Iso) stimulation of eAT leads to a downregulation of secreted proteins included in the GO terms 'cell redox homeostasis' and 'protein folding'. In addition, cardiac endothelial cells exhibit a downregulation in the expression of adhesion markers upon treatment with Iso-stimulated eAT derived conditioned media. Overall, these observations suggest thatUcp1 - associated metabolic activity plays a significant role in local tissue homeostasis within eAT and can plausibly alter its communication with neighboring cells of the cardiovascular system.